2008
DOI: 10.1111/j.1365-2672.2007.03708.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of amino acids and dipeptides by Lactobacillus plantarum from orange in nutritionally stressed conditions

Abstract: Aims:  To investigate amino acid and dipeptide utilization by Lactobacillus plantarum N4 isolated from orange peel, in a nutritionally depleted medium based on MRS (Mann, Rogosa, Sharpe). Methods and Results:  In MRS with 0·1 g l−1 of meat extract and without peptone and yeast extract, growth increased when essential and stimulatory amino acids and nonessential amino acid were added to the medium. Replacement of the essential amino acid, leucine, and the nonessential amino acid, glycine, by leucyl‐leucine (Leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Our results also showed that expression levels of intracellular oligoendopeptidases (pepF1 and pepF2) of L. sakei strain La22 were high in meat medium, similar to results in previous studies [16,24]. Some lactobacillus, for example L. lactis, can transport and metabolize certain amino acids when the carbohydrate source is exhausted, and these amino acids were from peptides hydrolyzed by internal endopeptidases rather than being free amino acids transported from outside the cell [26,27]. Even in L. sanfranciscensis and L. plantarum, transport of single amino acids was inefficient [28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results also showed that expression levels of intracellular oligoendopeptidases (pepF1 and pepF2) of L. sakei strain La22 were high in meat medium, similar to results in previous studies [16,24]. Some lactobacillus, for example L. lactis, can transport and metabolize certain amino acids when the carbohydrate source is exhausted, and these amino acids were from peptides hydrolyzed by internal endopeptidases rather than being free amino acids transported from outside the cell [26,27]. Even in L. sanfranciscensis and L. plantarum, transport of single amino acids was inefficient [28].…”
Section: Discussionsupporting
confidence: 91%
“…ClpE and ClpL are Clp proteins that function as chaperones and form the Clp proteolytic complex together with a structurally unrelated ClpP peptidase to specifically degrade misfolded proteins. ClpE belongs to the CtsR regulon and ClpL is the only one of degradation function of CtsR in all of the Clp‐related proteins . This may be explained why the two genes showed opposite expression in our study.…”
Section: Discussionmentioning
confidence: 62%
“…Whey and peptone are complex ingredients which contain several essential amino acids and important minerals and vitamins [22,26,30]. Bevilacqua et al [2] have shown that biomass production increased in a nonlinear way with increasing lactose up to a threshold value (20 g l -1 ) and for pH (6.0), but found that the effect of the interaction of pH and lactose in the model on biomass was small.…”
Section: Plackett-burman Experimental Designmentioning
confidence: 96%
“…(1999) reported that L. plantarum N4 and N8 isolated from oranges peal were able to derive energy and ammonia from arginine or citrulline catabolism, which is interesting for micro‐organisms developing in a stressful environment. Saguir et al. (2008) demonstrated the ability of L. plantarum N4 to assimilate mainly dipeptides rather than amino acids in nutritionally deficient condition.…”
Section: Introductionmentioning
confidence: 98%